The long shadow of Vatican II : living faith and negotiating authority since the Second Vatican Council - Rompay, Lucas van; Miglarese, Sam R.; Morgan, David (The University of North Carolina Press, 2015)
With the Second Vatican Council (1962-65), the Roman Catholic Church for the first time took a positive stance on modernity. Its impact on the thought, worship, and actions of Catholics worldwide was enormous. Benefiting from a half century of insights gained since Vatican II ended, this volume focuses squarely on the ongoing aftermath and reinterpretation of the Council in the twenty-first century.